2021
DOI: 10.1038/s41467-021-24607-6
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast transcriptome indicates SFRP2hi fibroblast progenitors in systemic sclerosis skin

Abstract: Skin and lung fibrosis in systemic sclerosis (SSc) is driven by myofibroblasts, alpha-smooth muscle actin expressing cells. The number of myofibroblasts in SSc skin correlates with the modified Rodnan skin score, the most widely used clinical measure of skin disease severity. Murine fibrosis models indicate that myofibroblasts can arise from a variety of different cell types, but their origin in SSc skin has remained uncertain. Utilizing single cell RNA-sequencing, we define different dermal fibroblast populat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
162
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 78 publications
5
162
1
Order By: Relevance
“…In healthy primary epithelial cells, increased SFRP4 expression was also associated with TGFinduced EMT, shown by increased expression of mesenchymal markers collagen, Vimentin, Snail and N-cadherin, decreased epithelial marker E-cadherin and altered cuboidal to elongated cell morphology. Further studies are needed to determine the putative role of SFRP4 in EMT and whether this is involved in myofibroblast differentiation, since previously SFRP4 has been shown to be a marker of this subset of SSc fibroblasts [32]. Previous observations show strong correlation between SFRP4 and other Wnt-related gene expression, including WIF1 and WNT2, in SSc skin and fibrosis [15,16,32,33]; thus, it is likely that SFRP4 is a marker for aberrant Wnt signalling, and warrants further research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In healthy primary epithelial cells, increased SFRP4 expression was also associated with TGFinduced EMT, shown by increased expression of mesenchymal markers collagen, Vimentin, Snail and N-cadherin, decreased epithelial marker E-cadherin and altered cuboidal to elongated cell morphology. Further studies are needed to determine the putative role of SFRP4 in EMT and whether this is involved in myofibroblast differentiation, since previously SFRP4 has been shown to be a marker of this subset of SSc fibroblasts [32]. Previous observations show strong correlation between SFRP4 and other Wnt-related gene expression, including WIF1 and WNT2, in SSc skin and fibrosis [15,16,32,33]; thus, it is likely that SFRP4 is a marker for aberrant Wnt signalling, and warrants further research.…”
Section: Discussionmentioning
confidence: 98%
“…Further studies are needed to determine the putative role of SFRP4 in EMT and whether this is involved in myofibroblast differentiation, since previously SFRP4 has been shown to be a marker of this subset of SSc fibroblasts [32]. Previous observations show strong correlation between SFRP4 and other Wnt-related gene expression, including WIF1 and WNT2, in SSc skin and fibrosis [15,16,32,33]; thus, it is likely that SFRP4 is a marker for aberrant Wnt signalling, and warrants further research. Additional studies are needed to determine whether SFRP4 and EMT is a pathologic step in fibrosis of SSc and sclGVHD.…”
Section: Discussionmentioning
confidence: 98%
“…To further extend our exploration of the T cells present in cutaneous lupus, we sought to compare our data to T cells from the skin of another rheumatic disease. A recent study focused on systemic sclerosis (SSc) obtained skin biopsies from 27 patients with SSc and an additional 10 healthy controls (20,28). After isolating T cell transcripts from this data, we integrated the dataset with our dataset of cutaneous lupus T cells, providing a unified visualization of both sets in the same UMAP space (Figure 4A).…”
Section: Elevated Ifn Signatures In Skin-localized T Cells From Lupus...mentioning
confidence: 99%
“…As in lung fibrosis, the development of skin fibrosis is also driven mainly by fibroblasts and myofibroblasts ( 100 ). A largescale study by Tabib et al ( 92 ) showed that the transcriptional profile of SSc dermal fibroblasts changed significantly compared to healthy dermal fibroblasts. They identified a new fibroblast subcluster from SSc patients that expressed PRSS23 and had upregulated expression of genes involved in extracellular matrix and collagen fibril organization, wound healing, and skeletal system development.…”
Section: Application Of Scrna-seq In Autoimmune Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…Within the PRSS23 + cluster, a second population (SFRP2 + , SFRP4 + ), identified as myofibroblasts, was found exclusively in SSc skin. The pseudo-time analysis showed that the SFRP2 hi fibroblasts were the immediate progenitors of myofibroblasts, however only a fraction of SFRP2 hi SSc fibroblasts differentiated into myofibroblasts, which is driven by upstream transcription factors, including FOSL2, RUNX1, STAT1, FOXP1, IRF7, CREB3L1, and SMAD3 ( 92 ). A subsequent study by the same group focused on skin myeloid cell populations and revealed 12 myeloid cell clusters, three of which were specifically identified in SSc skin.…”
Section: Application Of Scrna-seq In Autoimmune Inflammatory Rheumatic Diseasesmentioning
confidence: 99%